PROSIKLIKALITAS SEKTOR PERBANKAN DAN FAKTOR FAKTOR YANG MEMPENGARUHI - G.A. Diah Utari; Trinil Arimurti; Ina Nurmalia Kurniawati (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2012)
Procyclicality of bank’s credit local is a logical consequence of a process by which the financial sector finances economic growth. Bank’s will lend higher when the economy in boomin and will reduce lending on the opposite conditions. Excessive procyclicality potentially cause instability in the financial sector. This study aims to analyze the extent to which procyclicality of credit occured in the banking sector and analyze the factors that could potentially increase the procyclicality condotion. We used monthly series data from 2000 to 2012 and monthly 86 panel data bank since 2007 until 2010. The aggregate monthly data series were tested using simple regression equation and VAR while panel data are tested using panel data regression. Empirical result indicate the presence of procyclicality. Procyclicalityeffect tends to be stronger in periods of expansion than in contraction period. Bank’s procyclicality behavior is influenced by macro variables ( economic growth), the tendency of bank’s to rely on colleteral in credit assement, the level of banks risk, the condition of capital, banks size and ownership of banks( foreign banks and domestic banks)